SINTESIS HIDROKSIAPATIT DARI BATU KAPUR ALAM SECARA MEKANOKIMIA DENGAN VARIASI WAKTU PENGGILINGAN - Riqti, Frederica Thalita; Windarti, Tri; Sutanto, Heri (Chem Info Journal, 2013)
A study entitled synthesis of hydroxyapatite from natural limestone with variations mechanochemical milling time. The purpose of this research was to produce hydroxyapatite and to determine the effect of milling time on the purity, phases, and crystallite size on the synthesis of hydroxyapatite from limestone with mechanochemical method. The principle of this method is that the reaction between solids with the help of mechanical energy. Limestone that has been mashed mixed with powdered KH2PO4, mechanochemical process is then performed with the variation of time 0, 70, 80, 90, and 100 minutes. The resulting products were analyzed with FTIR and XRD and calculated by Scherrer equation to determine the crystallite size. Based on XRD and FTIR result, dominant types of calcium phosphate produced in this research were hydroxyapatite (HA) and tetracalcium phosphate (TTCP). Crystallite size of HA was formed on the time variation of 70, 80, 90, and 100 minutes ie 40.66 nm, 39.03 nm, 36.84 nm, and 39.78 nm.